A Retrospective Study: Re-examining the Established Narrative on the Association Between Maternal Chronic Energy Deficiency and Low Birth Weight in the Work Area of Air Naningan Public Health Center - Wulandari, Eka tri; Oktaviana, Metalia; Puspita, Linda; Wulandari, Ririn (Excellent Midwifery Journal, 2026)
Chronic Energy Deficiency (CED) in pregnant women remains a major nutritional concern and is widely recognized as a determinant of adverse perinatal outcomes, including Low Birth Weight (LBW). In the work area of Air Naningan Public Health Center, both CED and LBW remain prevalent, prompting the need for further evaluation of their association. This retrospective study aimed to analyze the relationship between maternal CED and LBW and to explore the observed mismatch in which many CED mothers still delivered normal-weight infants.This study used a retrospective analytic design involving 265 pregnant women who delivered in 2024. Data were extracted from electronic maternal cohort records (e-Kohort). Bivariate analysis using Chi-Square demonstrated a significant association between CED and LBW (χ² = 17.768; p < 0.001). The odds ratio (OR = 5.586; 95% CI: 2.337–13.354) indicated that pregnant women with CED had a 5.6-fold higher risk of delivering LBW infants. The prevalence of CED was 34.0%, while LBW occurred in 10.2% of births. Interestingly, 78.9% of CED mothers still delivered normal-weight infants, highlighting the multifactorial nature of LBW.These findings confirm CED as a strong predictor of LBW while emphasizing the importance of comprehensive maternal health interventions